2019
DOI: 10.1101/554121
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The foveal visual representation of the primate superior colliculus

Abstract: 13Processing of foveal retinal input is important not only for high quality visual scene analysis, but 14 also for ensuring precise, albeit tiny, gaze shifts during high acuity visual tasks. The 15 representations of foveal retinal input in primate lateral geniculate nucleus and early visual 16 cortices have been characterized. However, how such representations translate into precise eye 17 movements remains unclear. Here we document functional and structural properties of the foveal 18 visual representatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 69 publications
(161 reference statements)
4
25
0
Order By: Relevance
“…We asked two monkeys (P and N) to maintain steady fixation on a central spot. Prior work has shown that this condition gives rise to frequent microsaccades, which are associated with movement-related bursts in the rostral region of the SC representing small visual eccentricities and movement vectors (Hafed et al, 2009; Hafed and Krauzlis, 2012; Chen et al, 2019; Willeke et al, 2019). In experiments 1 and 2, we then presented a visual stimulus at a more eccentric location, and we recorded neural activity at this location (Fig.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We asked two monkeys (P and N) to maintain steady fixation on a central spot. Prior work has shown that this condition gives rise to frequent microsaccades, which are associated with movement-related bursts in the rostral region of the SC representing small visual eccentricities and movement vectors (Hafed et al, 2009; Hafed and Krauzlis, 2012; Chen et al, 2019; Willeke et al, 2019). In experiments 1 and 2, we then presented a visual stimulus at a more eccentric location, and we recorded neural activity at this location (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…We first tested the hypothesis that visually-induced action potentials can occur in the SC intra-saccadically; that is, putatively simultaneously with motor-related bursts. We exploited the topographic nature of the SC in representing visual and motor space (Cynader and Berman, 1972; Robinson, 1972; Chen et al, 2019). We asked two monkeys (P and N) to maintain steady fixation on a central spot.…”
Section: Resultsmentioning
confidence: 99%
“…However, again here, it is surprisingly hard to find literature on detailed individual RF mappings near the vertical and horizontal meridians. Based on our own experience, we find that RF's near the vertical meridian seem to still have preference for the contralateral side even when their RF's extend spatially in the ipsilateral hemifield (Chen et al 2019;Hafed and Chen 2016). That is, the RF hotspot location is still lateralized even when the RF extent does cross the vertical meridian discontinuity.…”
Section: Discussionmentioning
confidence: 76%
“…For example, in the SC, it is thought that the locus of activity on the SC map defines the desired saccade amplitude and direction (Cynader and Berman 1972;Lee et al 1988;Robinson 1972;van Opstal et al 1991;Wurtz and Goldberg 1972a;1971). Thus, the anatomical location of a neuron dictates the vector that it represents, resulting in a topographic map (Chen et al 2019;Cynader and Berman 1972;Hafed and Chen 2016;Robinson 1972). However, due to lateralization, there is a structural discontinuity in this map, with the visual field being divided along the vertical meridian into a left and right SC representation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation